2021
DOI: 10.3389/fimmu.2021.691032
|View full text |Cite
|
Sign up to set email alerts
|

Association of NRAS Mutation With Clinical Outcomes of Anti-PD-1 Monotherapy in Advanced Melanoma: A Pooled Analysis of Four Asian Clinical Trials

Abstract: BackgroundAnti-PD-1 monotherapy is the standard therapy for advanced melanoma patients, including those with NRAS mutations. The influence of NRAS mutation on immunotherapy, especially in noncutaneous melanoma, is largely uncharacterized.Materials and MethodsWe analyzed clinical data of four clinical trials for advanced melanoma patients treated with anti-PD-1 monotherapy between 2016 and 2019. The impact of NRAS mutation on efficacy and outcome of immunotherapy were analyzed in cutaneous and noncutaneous grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Patient demographics and baseline clinical characteristics are summarized in Table 1 . The median age (range) was 61 ( 33 –73) years, most patients had an ECOG PS of 0 [32/43 (74.4%)], and 23 (53.5%) patients had metastatic disease. The median baseline sum of diameters of target lesion was 36.3 mm (range 10.0–217.0).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient demographics and baseline clinical characteristics are summarized in Table 1 . The median age (range) was 61 ( 33 –73) years, most patients had an ECOG PS of 0 [32/43 (74.4%)], and 23 (53.5%) patients had metastatic disease. The median baseline sum of diameters of target lesion was 36.3 mm (range 10.0–217.0).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, NRAS mutations were found to be associated with better outcomes in patients with metastatic melanoma ( 31 ), while another study showed that NRAS mutations had no impact on the outcomes of immunotherapy ( 32 ). However, in a pooled analysis of four clinical trials conducted in Asia, NRAS mutations were associated with worse outcomes of immunotherapy ( 33 ). Therefore, the effect of NRAS on the efficacy of immunotherapy is unknown and needs to be verified in large-scale prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…We previously retrospectively analyzed the association of NRAS mutation status with the clinical outcomes of anti-PD-1 monotherapy in advanced melanoma, which showed that the PFS and OS of patients with NRAS mutation were shorter than those of patients without NRAS mutation in cutaneous and acral/mucosal melanoma. 38 Kirchberger et al also reported that survival is less favorable in immune checkpoint inhibitor-treated patients with NRAS mutation. 39 Therefore, the high mutation frequency of RAS family might be another reason for a better response to anti-PD-1 and the highly aggressive nature of PMME compared with NEMM.…”
Section: Discussionmentioning
confidence: 98%
“…The t -test in the present study revealed a significant reduction of BUN, SCR, TNF- β 1, VEGF, TIMP-1, and MMP-2 after treatment, and the use of axitinib plus tislelizumab resulted in greater reduction, indicating that axitinib combined with tislelizumab can improve renal function, probably because the interplay of these two plays a central role in reducing tumor blood supply via blocking the formation of neovascularization, so as to inhibit the proliferation and growth of VEGF, reduce the angiogenesis for tumor nutrients provision, and inhibit the occurrence and growth of tumor cells [ 20 ]. Moreover, the tislelizumab immunotherapy drug binding to PD-1 on the tumor surface stimulates lymphocyte secretion, boosts the resistance to tumor cells, attenuates or even reverses T cell disability or failure, reactivates the attack and killing ability of effector T cells, and enhances tumor resistance [ 21 ]. The action of the combination can restore the renal function accordingly.…”
Section: Discussionmentioning
confidence: 99%